Suppressive effects of the supercritical-carbon dioxide fluid extract of Chrysanthemum indicum on chronic unpredictable mild stress-induced depressive-like behavior in mice. Issue 2 (11th February 2019) - Wu, Xiaoli; Tang, Benqin; Liao, Xian; Su, Ziren; Lee, Simon Ming-Yuen; Cai, Yefeng; Li, Chuwen
Abstract : The aim of the present study was to explore whether the supercritical-carbon dioxide fluid extract from flowers and buds of Chrysanthemum indicum (SEC) exhibits antidepressant-like effects in a chronic unpredictable mild stress (CUMS)-induced mice model. Abstract : The aim of the present study was to explore whether the supercritical-carbon dioxide fluid extract from flowers and buds of Chrysanthemum indicum (SEC) exhibits antidepressant-like effects in a chronic unpredictable mild stress (CUMS)-induced mice model. Firstly, SEC was found to reverse a CUMS-induced decrease in the body weight gain in mice. Next, SEC was found to alleviate CUMS-induced depressive-like behavior, evidenced by the reversal of the decrease in the sucrose consumption in the sucrose preference test (SPT), the increase in the locomotor activity in the open field test (OPF), and the alleviation of immobility duration in both the forced swimming test (FST), and tail-suspension test (TST). SEC also attenuated CUMS-induced hyperactivity of the hypothalamic-pituitary-adrenal (HPA) axis by decreasing the levels of serum corticosterone and (CORT) and adrenocorticotropic hormone (ACTH), and hypothalamus corticotrophin-releasing hormone (CRH). In addition, SEC was found to suppress the expression of pro-inflammatory cytokines, including the tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and IL-6 in the hippocampal of CUMS mice. Interestingly, further investigations demonstrated that SEC inhibited CUMS-induced activation of the nuclear factor kappa B (NF-κB) and NOD-like receptor protein 3 (NLRP3) inflammasomes pathways but upregulated brain-derived neurotrophic factor (BDNF) expression and promoted phosphorylation of extracellular signal-regulated kinase (ERK) and cAMP-response element-binding protein (CREB) in hippocampal. In summary, SEC was able to alleviate depressive-like behavior in a CUMS-induced mice model, accompanied by inhibitory roles in the hyperactivity of the HPA axis and pro-inflammatory cytokine expression. Modulating the NF-κB/NLRP3 and BDNF/CREB/ERK pathways contributed to SEC-mediated antidepressant-like effects.